Professional judgement: an institutional logic approach to contractor tender pricing. Issue 1 (26th July 2022) - Jefferies, David; Schweber, Libby
Competitive tendering is the default procurement route for most types of construction projects in the UK. As a process, it is costly, time-consuming and complicated, involving input from upwards of 200 separate organisations per project. Existing research has mainly focused on identifying discrete factors that influence contractor pricing. While many scholars and professionals treat the level of mark-up as a technical problem, others acknowledge the role of professional judgement. This paper uses the neo-institutional concept of 'hybrid institutional logics' and an exploratory study into two projects in one firm to explore the way in which different types of professionals work together to produce a single price. The research documents the existence of two distinct logics: a first-principles cost estimation logic and strategic mark-up logic. These are combined in a highly structured process, with moments of separation, bridging and demarcation. These findings explain how firms purposefully balance multiple cognitive schemas to manage resources and position themselves in the market. The research also offers a novel theoretical approach to the study of multidisciplinary collaboration which can be used to address issues of integration more generally. Practice relevance: A study of the ways in which main contractors balance multiple considerations when tendering offers several contributions to practice. First, it identifies how pricing is influenced by socially embedded professional judgements. These include judgements about: (1) the current market price (independent of supplier bids); (2) the firm's market position and relationship with clients, suppliers and competitors; and (3) firm-level resource management. Second, it identifies several specialised competencies that inform the use of 'intuition' in pre-tender pricing and which contribute to 'realistic' mark-ups, notably 'first-principles estimation' and 'strategic firm-level mark-up'. Third, it analyses the way in which these are mobilised across the tender preparation process, drawing attention to ways that distinct competencies are combined in bid preparation, in particular, and in everyday work processes, more generally.